Out of home care in Norway and Sweden - similar and different - Elisabeth Backe-Hansen; Ingrid Højer; Yvonne Sjöblom; Jan Storø (Psychosocial Intervention, 2014)
An overview of the current situation in the out-of-home care in Norway and Sweden is presented in this article; also the development in later years is described and discussed. Socially, politically and culturallythere are few differences between Norway and Sweden. Child protection and out-of-home placement of children and young people are integrated parts in the welfare state that are shared by the Nordic countries. It is a model that builds on principles of universalism and decommodification of social rights. The welfare model presupposes high public legitimacy for a high level of social expenditure. However the idea of marketization and privatization has also affected the welfare model in Sweden and Norway. Although there are more similarities than differences between the two countries' child protection systems, the article discusses some differences, for example the after care services, new groups of children and young people in the out-of-home care, like young unaccompanied asylum seekers. There are also some differences when it comes to privatization, the introduction of evidence-based methods in the child protection system and the tension between general and residual services for children and young people in the child protection system.